AN ANALYSIS OF THE NEGOTIATION OF MEANING AND FORM IN NATURAL EFL CLASSROOMS: A CASE STUDY AMONG PRE-SERVICE TEACHERS - Kusuma, Paulina Chandrasari; Indriyani, Christina Eli; Xenia, Tia (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
The present competence of language learners influences the process, particularly in modifying the input to ensure the exact level of comprehensibility they can manage. It involves the negotiation of meaning (NfM) and form (NfF). Teachers need to pay attention to how frequently both processes occur in classroom interaction and whether the teachers use this situation to enhance students’ language acquisition. Thus, this study aims to seek information concerning the negotiation of meaning and form in the natural classroom setting involving student teachers in a practicum program. To reach the objective of this study, two research questions will address: (1) Do negotiation of meaning and form take place in student-teacher-student interaction in a natural EFL classroom setting? (2) How do the student-teachers use negotiation of meaning and form strategies in the EFL classroom? Mixed method research will be employed by analyzing the utterances and conducting interviews. The analysis of the study reveals that firstly, NfM and NfF are two common occurrences in the student-teacher interaction in the natural EFL classroom under study; secondly, the strategies used by both NfM and NfF covered the negotiation processes with various moves and Long’s (1996) types of signals embracing confirmation check, clarification request, and comprehension check in certain circumstances. Eventually, this study brings profound implications in two areas, namely the design of a teacher training curriculum and the teaching pedagogy.